Opportunity to add skills in the field of rail development - Nor Salwana, Mohammad Idris (2021)
KUANTAN, 6 April 2021 - The selection of Universiti Malaysia Pahang (UMP) as the Tester Training Module training centre in the Industrial Skills Training Programme (PLKI ECRL) provides an opportunity for UMP to contribute towards the construction of the high-profile project of East Coast Rail Link (ECRL).